Adhesion Testing of a Denture Base Resin With 5 Casting Alloys - Nancy L. Clelland, DMD, MSD,1 Meade C. van Putten, DDS, MS,1 (Blackwell Synergy, 2000)
This study compared denture base resin shear bond strengths to silicoated Au-Pd, Au-Pd-Ag, Au-Ag-Pd-Cu, high-Pd, and Ni-Cr-Be alloys used to fabricate frameworks for hybrid implant prostheses. Microleakage between alloy and resin was also compared among groups after specimen fracture.